Management of Oroantral Communication Using Double Layered Closure with Buccal Fat Pad and Buccal Advancement Flap: Prospective Randomized Clinical Study (Medico Legal Update, 2020)
Introduction: Although many techniques are available for management of oroantral communication, theyutilize single layer tissue for closure of defect which is composite in nature. There is limited evidence inliterature regarding efficacy of double layered closure using combination of flaps. This study was designedto assess utility of double layer closure of oroantral communication using buccal fat pad and buccal mucosaadvancement flap.Material and Method: Patients with oroantral communication were randomly allocated to two groups;group A were treated with two layered closure (buccal fat pad and buccal mucosa) and group B were treatedwith single layer closure (buccal fat pad). Same protocol of perioperative management was used for bothgroups. The postoperative parameters evaluated included success of surgery (complete closure without anynasal regurgitation), duration of surgery, pain, swelling and mouth opening.Results: Total of 27 patients were divided into group A (n=13) and group B (n=14). The mean size of thedefect was 28.23 mm in study group and 24.57 mm in the control group. The surgical procedure took moretime (42.23 minutes) in group A, as compared to group B (26.21 minutes). Post-operative evaluation of painand mouth opening showed no statistically significant between the two groups at 7th and 30th postoperativedays respectively. However, swelling was relatively more when combination of buccal fat pad and buccaladvancement flap was used.Conclusion: Double layered closure is efficient in management of OAC. No dehiscence of flap was seen instudy group. Comparatively 3 dehiscence was observed in control group, especially with large size defect.The postoperative sequel in both groups was similar.